Sixteen-year incidence changes of four main disease classes in the North Caucasus - M. N. Mamedov; S. N. Mammaev; M. A. Umetov; Z. A. Toguzova; R. T. Didigova; S. G. Kechedzhieva (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To assess the changes of four main disease classes in the North Caucasus Federal District from 2005 to 2021.Material and methods. The incidence changes of cardiovascular diseases (CVDs), neoplasms, respiratory and endocrine diseases, as well as nutritional and metabolic disorders are analyzed. The disease incidence was assessed as registration of newly diagnosed diseases per 1 thousand people according to official data from Rosstat published in 2022.Results. In the North Caucasus region over the past 16 years, an increase in incidence rates has been observed for the main disease classes. The first place is occupied by CVDs, the number of which increased in 2021 compared to 2005 by 80%. The incidence of respiratory increased by 40%, while cancer by 20%. At the same time, the incidence of endocrine diseases, as well as nutritional and metabolic disorders decreased by 18%. In general, similar morbidity dynamics are observed for the first three disease groups. At the same time, in 2021, only for CVDs, the average incidence rates in the Russian Federation and the North Caucasian Federal District turned out to be comparable, and for cancer, respiratory, metabolic disorders and endocrine diseases in the North Caucasus Federal District, the incidence rates were lower compared to the Russian Federation as a whole. In some regions, both general trends and variability in the incidence of individual noncommunicable diseases are observed.Conclusion. The data obtained indicate that over a 16-year period, the incidence of CVDs, respiratory and cancer diseases has increased in the North Caucasus Federal District. This once again emphasizes the need for effective medical examination of the adult population and the implementation of primary prevention at the population level and among high-risk individuals.